Design and Synthesis of Ag Nanocluster Molecular Beacon for Adenosine Triphosphate Detection - Xiaoshuang Li; Hao Zhang; Ying Zhao; Lili Lian; Xiyue Wang; Wenxiu Gao; Bo Zhu; Dawei Lou (Journal of Analytical Methods in Chemistry)
This study presents a fluorescence method for detecting adenosine triphosphate (ATP) based on a label-free Ag nanocluster molecular beacon (MB) with high sensitivity. The sensor contains a hairpin-shaped MB, two short single-stranded DNA strands, and T4 DNA ligase. The MB consists of three parts, which are the template DNA sequence for synthesizing Ag nanoclusters at the 5′ end, the middle DNA with a hairpin-shaped structure, and the guanine base-rich DNA sequence at the 3′ end. The sensor exhibits high fluorescence intensity in the absence of ATP. However, when the probe is used for ATP detection, the two short DNA sequences in the sensor would form a long sequence by enzymatic ligation reaction; this long sequence opens the hairpin-shaped structure of the MB and decreases the fluorescence of the system. Under optimal analytical conditions, a clear linear relationship is observed between ATP concentration and fluorescence intensity in the range of 0.1–10 μM. The interference presented by other small molecules during ATP detection is evaluated, and results confirm the good selectivity of the proposed sensor. Compared with traditional methods, the sensor is label free, easy to operate, inexpensive, and highly sensitive.